2010
DOI: 10.1021/jm100442u
|View full text |Cite
|
Sign up to set email alerts
|

The Pthaladyns: GTP Competitive Inhibitors of Dynamin I and II GTPase Derived from Virtual Screening

Abstract: We report the development of a homology model for the GTP binding domain of human dynamin I based on the corresponding crystal structure of Dictyostelium discoidum dynamin A. Virtual screening identified 2-[(2-biphenyl-2-yl-1,3-dioxo-2,3-dihydro-1H-isoindole-5-carbonyl)amino]-4-chlorobenzoic acid (1) as a approximately 170 microM potent inhibitor. Homology modeling- and focused library-led synthesis resulted in development of a series of active compounds (the "pthaladyns") with 4-chloro-2-(2-(4-(hydroxymethyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 59 publications
0
53
0
Order By: Relevance
“…Quantitative high-throughput receptor-mediated endocytosis (RME) assays were performed as previously described (Hill et al, 2009;Odell et al, 2010) using Transferrin (Tfn) conjugated to Texas Red in untreated and siRNA-transfected HeLa cells for 10 min. Cells were then washed with ice-cold PBS and acid washed (0.2 M acetic acid/0.5 M NaCl, pH 2.8) for 15 min on ice.…”
Section: Endocytosis Assaymentioning
confidence: 99%
“…Quantitative high-throughput receptor-mediated endocytosis (RME) assays were performed as previously described (Hill et al, 2009;Odell et al, 2010) using Transferrin (Tfn) conjugated to Texas Red in untreated and siRNA-transfected HeLa cells for 10 min. Cells were then washed with ice-cold PBS and acid washed (0.2 M acetic acid/0.5 M NaCl, pH 2.8) for 15 min on ice.…”
Section: Endocytosis Assaymentioning
confidence: 99%
“…30 Each series thus far has targeted many of dynamin's four domains: the pleckstrin homology, the assembly domain, the proline-rich domain, and the GTP binding domain. Other reported dynamin inhibitors include dynasore, antipsychotics, and selective serotonin reuptake inhibitors.…”
Section: Scheme 1 Amentioning
confidence: 99%
“…C10 and D10 are among the most potent RME inhibitors reported, only surpassed by Dynole 34-2 (IC 50(RME) ∼ 5.0 μM). 28,30,36 The development of the Rhodadyn series adds another chemical biology probe to the expanding palette of dynamin inhibitors. …”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…24 is found to be the most active in the series (Gordon et al, 2013). Odell et al (2010) have reported series of compounds such as pthaladyns based on the homology model for the GTP-binding domain of human DNM1. Pthaladyan-23 was found to be a potent inhibitor of DNM1-mediated synaptic vesicle endocytosis in brain synaptosomes (Odell et al, 2010).…”
Section: Dynamin Function and Ligandsmentioning
confidence: 99%
“…Odell et al (2010) have reported series of compounds such as pthaladyns based on the homology model for the GTP-binding domain of human DNM1. Pthaladyan-23 was found to be a potent inhibitor of DNM1-mediated synaptic vesicle endocytosis in brain synaptosomes (Odell et al, 2010). Hill et al (2004Hill et al ( , 2005Hill et al ( , 2009 have reported amines and Dynoles for the inhibition of dynamin-mediated endocytosis.…”
Section: Dynamin Function and Ligandsmentioning
confidence: 99%